2016
DOI: 10.1136/jclinpath-2016-203656
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interactions of polo-like kinase 1 in human cancers

Abstract: Polo-like kinase 1 (PLK1) is an essential protein in communicating cell-cycle progression and DNA damage. Overexpression of PLK1 has been validated as a marker for poor prognosis in many cancers. PLK1 knockdown decreases the survival of cancer cells. PLK1 is therefore an attractive target for anticancer treatments. Several inhibitors have been developed, and some have been clinically tested to show additive effects with conventional therapies. Upstream regulation of PLK1 involves multiple interactions of prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 90 publications
0
29
0
Order By: Relevance
“…Of these target genes, FOXM1 and PLK1 are both critical proteins necessary for the initiation of mitosis or M phase 19, 20 . Due to their strong role in mitotic entry, both are found upregulated in many cancers 21, 22 . To identify the role of PGRB in the promotion of mitosis, RNA transcript levels of known mitotic-initiating proteins were evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these target genes, FOXM1 and PLK1 are both critical proteins necessary for the initiation of mitosis or M phase 19, 20 . Due to their strong role in mitotic entry, both are found upregulated in many cancers 21, 22 . To identify the role of PGRB in the promotion of mitosis, RNA transcript levels of known mitotic-initiating proteins were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…This work provided further detailed analysis of PGR binding directly at the loci of mitosis- promoting genes: Foxm1 , Plk1 , Cdc25c , and Cdk1 . Since PLK1 and FOXM1 are necessary for cell cycle progression 19 , they have consistently been identified to be expressed in a variety of cancers 21, 22 . PLK1 alone is found upregulated in human ovarian cancer 49, 50 , endometrial carcinoma 51 , ectopic endometriosis 52 , and breast cancer 53 , often correlating with increased proliferation and severity.…”
Section: Discussionmentioning
confidence: 99%
“…In order to complete this study, we chose to silence the biologically relevant endogenous polo like kinase 1 gene (Plk1) upregulated in many cancers. [24,25] This gene is implicated in cell cycle progression and its downregulation induces apoptosis. [26,27] Silencing of the expression of Plk1 by RNA interference with siPlk1 can be assessed directly by measuring the cell viability, as compared to delivery with control siRNA.…”
Section: Silencing Of a Gene Of Therapeutic Interestmentioning
confidence: 99%
“…The expression of MAP9 is downregulated in colorectal cancer, whereas AURKA and Plk1 are upregulated (Rouquier et al, 2014). Dysregulation of AURKA and Plk1 are strongly associated with tumorigenesis (Weng Ng et al, 2016;Al-Khafaji et al, 2017;Chen et al, 2017;Zhu et al, 2017), and AURKA polymorphisms have also been reported in association with GC and breast cancer (Lopez-Cortes et al, 2018;Mesic et al, 2017). Considering the direct interactions of MAP9 with AURKA and Plk1, we believe that MAP9 plays key role in carcinogenesis.…”
Section: Discussionmentioning
confidence: 83%